Análisis técnico- financiero del uso de la tecnología de fracturamiento con gas licuado de petróleo en la formación la luna de la Cuenca del Catatumbo (2019)
An view of the debates associated with the advantages and disadvantages of hydraulic fracturing in Colombia, a comparative analysis of the Colombian Regulations is presented in an objective way, in relation to other nations that have technically proposed the use of base fracture fluids. liquefied petroleum gas (LPG). This allows to determine what improvements could be made to the current legislation, around the fluids used for the development of the fracturing technique. In addition, it seeks to determine the technical and financial feasibility using as a base fluid LPG, by simulating a fracture, making use of a fluid with analogous properties (Selected by a state of the art), which adapt to the geology present in the formation Moon; geological unit located in the sedimentary basin of Catatumbo- Colombia. Likewise, it is planned to carry out a financial analysis regarding the implementation of said technology, through indicators.